Evaluation of cognitive tasks of infants in socio-environmental vulnerability using a short version of WISC IV - Adrian Israel Yañez Quijada; Beatriz Olivia Camarena Gómez; Raúl Morales Villegas (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales, 2020)
The objective of the study described in this article was to associate social vulnerability with cognitive performance in groups of children living in contexts of environmental threat. The research design was non-experimental, correlation-comparative, and carried out in two phases. Children from six to twelve years old, residing in Hermosillo, Sonora, Mexico (n = 432), 88.2% in agricultural localities and the remaining 11.8% in urban context participated, in the first phase 184 subjects participated and in the second 248. Indicators of the Social Vulnerability, the AMAI test, the progressive matrix scale and the WISC IV test were used. In results, a negative correlation was observed between social vulnerability in threat contexts and cognitive performance (r = -.437); and two clusters were identified, the so-called "Greater Social Vulnerability" (n = 115) and the named "Less Social Vulnerability" (n = 41). The study concluded on the need to integrate biophysical and social variables to the analysis of the cognitive performance of infants.